Features of the manifestation of subjective well-being as an indicator of a person's mental health (on the example of state employees) - Fedotova, Tetiana (Psychological Prospects Journal, 2018)
In the article it is theoretically observed the problem of mental health in the framework of various psychological theories of the individual (A. Adler, B. Skinner, E. Ericson, A. Bandura, A. Maslow). One of its main indicators – psychological well-being, subjectively expressed in the happiness, feelinging of positive emotions, satisfactioning one's own life.The features of the manifestation of subjective well-being as indicator of mental health by civil servants are determined empirically, taking into account: age, seniority of work and specifics of work. In the groups of employees who were divided according to the age criterion, is required by such clusters attention : «signs accompanying the basic psychoemotional symptomatology» and «tension / sensitivity» – in the group of persons 30-40 years old; «mood change» – in the group of persons 40-50 years old; «the importance of the social environment», «self-assessment of health» and «satisfaction with daily activities» – in the group of people over 50 years old. Seen the growth of the importance of clusters «strength and sensitivity», «signs that accompany the basic psycho-emotional symptomatology» and «degree of satisfaction with everyday activity» and the peak of their manifestation in persons with work experience of 10-15 years; the absence of significant differences of the cluster of «mood change» in respondents, regardless of their length of work; the importance of clusters «the significance of the social environment» and «self-esteem of health» in the group of those with an employment of more than 20 years. It has been found that state employees, which working with people, are characterized by high spirits and optimistic outlook for the future, they are also satisfied with daily activities. Respondents who work with documents and information, except for a heightened mood and optimistic outlook on the future, attach importance to the nearest social environment.
Keywords: mental health, subjective well-being, cluster.